Accelerated Multi‐Stage Synthesis of Indium Phosphide Quantum Dots in Modular Flow Reactors. Issue 4 (29th January 2023) - Epps, Robert W.; Delgado‐Licona, Fernando; Yang, Hyeyeon; Kim, Taekhoon; Volk, Amanda A.; Han, Suyong; Jun, Shinae; Abolhasani, Milad
Abstract: Development and scalable nanomanufacturing of high‐quality heavy metal‐free quantum dots (QDs) with high‐dimensional experimental design spaces still remain a challenge. In this work, a universal flow chemistry framework for accelerated fundamental and applied studies of heavy metal‐free QDs with multi‐stage chemistries is presented. By introducing flexible time‐ and temperature‐to‐distance transformation using modular fluidic blocks, an in‐flow synthetic route of InP QDs with the highest reported first excitonic absorption peak to valley ratio is unveiled  with a reaction time one order of magnitude faster than batch reactors. The flexible time‐ and temperature‐to‐distance transformation as an enabling factor for generalization of flow reactors toward the accelerated discovery, development, and nanomanufacturing of high‐quality emerging nanomaterials for next‐generation energy, display, and chemical technologies is discussed. Abstract : This work presents a universal and modular flow chemistry strategy for accelerated fundamental and applied studies of heavy metal‐free quantum dots (QDs) with multi‐stage chemistries. Leveraging a flexible time‐ and temperature‐to‐distance transformation using modular fluidic blocks, the in‐flow synthetic route of high‐performing heavy metal‐free QDs with a reaction time one order of magnitude faster than batch reactors is unveiled.